FIGURATIVE AND LEXICAL VARIETIES IN FACEBOOK POSTS - Widiadnya Putri, I Gusti Ayu Vina; Andri Permana, I Putu; Nova Winarta, Ida Bagus Gde (Lingual Journal of Language and Culture; Vol 4 No 2 (2017), 2017)
Language is a highly elaborated signaling system. It serves various functions in communication, it is used to share ideas, convey feelings and emotions, etc. The researchers are interested to uncover more on how people use language in terms of its variety and lexical in one of the popular social media networking platforms that we all know as Facebook. Based on the aforementioned background of the study, the problem of the research can be formulated as follows: (1) what are the figurative languages used in Facebook posts by female and male Facebook users? (2) How are the emotional lexical varieties e.g. used in Facebook posts? Method of research is a procedure needed to do the research better. In this case, method of research covers data source, data collection and data analysis. The data of this research have been taken from facebook profile , it is as an online social networking website where people can create profiles, share information such as photos and quotes about themselves, and respond or link to the information posted by others. The method that used in collecting data is method of library research. They are collected by reading the Facebook user’s post, by underlining and note taking as well. The data analysis is the last step in this process of writing this research. The analysis is done by descriptive method. To make the analysis clearer, all of examples are completed with explanation. Referring to the first research problem, there are some figurative languages used by the Facebook users such as, Simile (female 1 or 4.3% and male 0%), Metaphor (female 4 or 17.3% and male 0%),, Personification (female 3 or 1.3% and male 1% or 4.3%),, Hyperbole (female 4 or 17.3% and male 1 or 4.3%), and Idiom (female 3 or 13% and male 0%),. Furthermore, in regards to the second problem that is emotional lexical used by the Facebook Users, we could mention that both the Augmentatives (female 3 or 13% and male 1 or 4.3%), and Euphemisms (female 1 or 4.3% and male 1 or 4.3%), are used in the Facebook posts Keywords: Figurative, lexical variety, Facebook, Post